Electronic scheme simulator usage for pmt model creation - Бочаров, Олег Александрович (Eastern-European Journal of Enterprise Technologies, 2011)
This article grounds necessity of photomultiplier tube (PMT) model creation by means of computer circuit simulator, basic departure data for model creation are given, model scheme and results of it testing by means of computer circuit simulator are present